Longitudinal Changes in Body Weight of Breastfeeding Mothers in the First Year after Delivery and its Relationship with Human Milk Composition: a Combined Longitudinal and Cross-sectional Cohort Study - Huijuan Ruan; Yajie Zhang; Qingya Tang; Xuan Zhao; Xuelin Zhao; Yi Xiang; Wei Geng; Yi Feng; Wei Cai (Food Science and Human Wellness)
Objective: Postpartum weight retention (PPWR) is a common problem among women after childbirth. The main objectives of this study are to understand the changes in body weight of breastfeeding mothers during long-term follow-up and preliminarily explore the relationship between maternal body weight and human milk composition, including macronutrients, leptin, and adiponectin. Methods: The study included a longitudinal cohort (122 mothers), and a cross-sectional cohort (37 mothers). The human milk, maternal weight, and dietary surveys were collected in the longitudinal cohort at different follow-up time points (1−14 days postpartum, 2−4 months postpartum, 5−7 months postpartum, and 12−17 months postpartum). The maternal body weight was analyzed using the responses in the survey questionnaires. A milk analyzer based on the mid-infrared spectroscopy (MIRS) was used to determine milk composition, and nutrition analysis software evaluated dietary intakes. In the cross-sectional cohort, participating mothers were asked to provide blood and human milk samples and pertinent information related to maternal body composition. Maternal body composition was measured by bioelectrical impedance analysis (BIA), while ELISA analyzed leptin and adiponectin in milk and serum. Results: At 5−7 months postpartum, the PPWR of breastfeeding mothers was (2.46 ± 3.59) kg. At 12−17 months postpartum, the PPWR was (0.98 ± 4.06) kg. PPWR was found to be negatively correlated with milk fat content within 14 days postpartum and positively correlated at 2−4 months postpartum. In addition, the maternal weight and body muscle mass were positively correlated with leptin and adiponectin in milk. Plasma leptin was positively correlated with the mother's body weight, body mass index (BMI), FAT percentage, and body fat mass, while plasma adiponectin did not correlate with any parameter. The results also indicate that the PPWR did not correlate with leptin and adiponectin in plasma or milk. Conclusions: Breastfeeding mothers may retain considerable weight gain one year after delivery. Human milk composition may be related to changes in maternal body weight. Leptin and adiponectin in breast milk and leptin in plasma are associated with the maternal body composition. This study supports the notion that maternal nutritional status may affect offspring health through lactation, and future research should focus on exploring weight management of postpartum mothers.